Woman's empowerment and Islam: the UN Beijing document platform for action - Kausar, Zeenath (Ilmiah Publishers, 2002)
Despite several worldwide feminist movements for the liberation and emancipation of women and several international conferences for the empowermnet of women, the overall advancement achieved by women was less than satisfactory. Hence, the United Nations Organizations held its Fourth World Conference On Women (FWCW) in Beijing, China, in 1995. In this conference, the epoch-making document, Platform for Action was passed. Although some of the demands of the documents are comendable, but some demands particularly on sexual reproductive health are not acceptable to all cultures and societies around the world. In this book, Women's Empowerment and Islam: The UN Beijing Document Platform for Action, some of he critical demands of the document are explored and analysed. It is argued that the document is greatly influenced by the sexual politics of modern and postmodern feminists. It is pointed out that the document is an attempt at colonization and aims to promote new world order ignoring other cultures and traditions across the world.